The Impacts of Malnutrition Status and Relevant Factors on Preschool Children in Cao Ma Po Commune, Quan Ba District, Ha Giang Province - Tam, Vu Van; Nhan, Nguyen Huu; Tinh, Hoang Quy; Hung, Nguyen Phuc (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abtract: This study was conducted to evaluate malnutritional status and related factors on 388 preschool children in Cao Ma Po commune, Quan Ba district, Ha Giang province. Anthropometric indicies including weight for age, height for agewere used to assess children malnutrition status. Furthermore, we investigated and interviewed parents, teachers to find out related factors to children malnutriotional status in this research area. Results showed that the development of these anthropometric parameters of preschool children followedthe rules of body growth of Vietnamese people. Anthropometric indicies of preschool children in Cao Ma Po were lower than the general values ofVietnam people. Malnutrition percentage of children was relatively high (underweight: 24.8%; stunting: 77.3%; wasted: 4.5%). Factors related to children malnutritional status were job and education level of parents, water source used in household, children weaning time. Keywords: Malnutrition status, related factors, Cao Ma Po.